Mixed Capillary Venous Retroperitoneal Hemangioma. (28th February 2013) - Godar, Mohit; Yuan, Qinghai; Shakya, Rukeshman; Xia, Yang; Zhang, Pengguo
Abstract : We report a case of mixed capillary venous hemangioma of the retroperitoneum in a 61-year-old man. Abdominal ultrasonography showed a mass to be hypoechoic with increased flow in color Doppler imaging. Dynamic contrast-enhanced computed tomography revealed a centripetal filling-in of the mass, located anterior to the left psoas muscle at the level of sacroiliac joint. On the basis of imaging features, preoperative diagnosis of hemangioma was considered and the mass was excised by laparoscopic method. Immunohistochemical studies were strongly positive for CD31 and CD34, and negative for calretinin, EMA, WT1, HMB45, Ki67, synaptophysin, and lymphatic endothelial cell marker D2–40. Histologically, the neoplasm was diagnosed as mixed capillary venous hemangioma.